ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH - Alex Zami (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
Carrying out good governance is a necessity. The government offers quality services with the value of transparency, clean, and on target, all of that can be seen in the local government performance report. This study aims to analyze the financial performance of Banten province by using quantitative methods. The sample in this study amounted to 40 local government financial statement data from 4 cities and 4 districts of Banten Province and used the Saturated sampling technique. The results showed that financial performance was highly dominated by supervision, whereas audit opinion has less effect. This finding explains that the role of board members in discussing finance with local governments must be comprehensive, so that the budget can be right on target. However, the government should be pay attention to BPK assessment so that performance increases. Keywords: Supervision, Audit Opinion, Performance